2022
DOI: 10.22282/ojrs.2022.98
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Egzersi̇z Bağimlilik Düzeyleri̇ni̇n İncelenmesi̇

Abstract: Araştırmanın amacı üniversitelerin farklı birimlerinde öğrenim gören üniversite öğrencilerinin egzersiz bağımlılık düzeylerinin incelemektedir. Araştırmaya 10 farklı fakültede ve yüksekokulda öğrenim gören toplamda 208’i erkek 296’sı kadın olmak üzere 504 kişi katılmıştır. Araştırmada tarama yöntemi kullanılmıştır. Araştırmada veri toplama aracı olarak “Kişisel Bilgi Formu” ve “Egzersiz Bağımlılığı Ölçeği” kullanılmıştır. Elde edilen verilerin analiz işlemlerinde, katılımcıların demografik özelliklerini belirl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Yıldızdal (45) examined the effect of exercise addiction on psychological endurance in swimmers and found no difference between the age factor and exercise addiction levels of the participants. Çingöz and Mavibaş (12), on the other hand, did not find a significant difference in exercise addiction levels depending on the age factor in their study in which the sample group consisted of university students studying in different fields. As can be seen, there are studies in the relevant literature that are in parallel with the findings of our study, as well as studies that do not show parallelism.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Yıldızdal (45) examined the effect of exercise addiction on psychological endurance in swimmers and found no difference between the age factor and exercise addiction levels of the participants. Çingöz and Mavibaş (12), on the other hand, did not find a significant difference in exercise addiction levels depending on the age factor in their study in which the sample group consisted of university students studying in different fields. As can be seen, there are studies in the relevant literature that are in parallel with the findings of our study, as well as studies that do not show parallelism.…”
Section: Discussionmentioning
confidence: 78%
“…In this context, an athlete and an individual who exercises are differentiated. In the relevant literature, when the studies on exercise addiction are examined, it is seen that the research group consists of individuals who are athletes (3,5,7,8,13,22,24,27); there are also studies in which the research group consists of individuals who are not athletes but exercise (12,17,20,26,39,44). Considering this remarkable situation, it is recommended that the concept of exercise and sport should be taken into consideration when determining the research group in the studies to be conducted on exercise addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Although exercise is generally seen as a positive behaviour due to its physical, physiological and psychological benefits [3,4], it has recently been observed that excessive physical activities can also cause negative effects such as exercise addiction [5,6,7,8]. Exercise addiction, which is described as the "dark side" of exercise and a disease that negatively affects human health, has recently been addressed by many researchers [9,10,11,12].…”
Section: Introduction 1èmentioning
confidence: 99%
“…Although many studies have been conducted on exercise addiction, it has been observed that studies have intensi ed in recent years (Çingöz & Maviḃaş, 2022;Dervişoğlu et al, 2022;Dinardi et al, 2021;Lukács et al, 2019;Üstün & Oz, 2022). It is seen that the exercise addiction levels of football players and university students were determined generally in these studies.…”
Section: Introductionmentioning
confidence: 99%